2013
DOI: 10.3390/ijms14058818
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Channels Mediated by m2mAChR and α9nAChR Co-Exist in Type II Vestibular Hair Cells of Guinea Pig

Abstract: Acetylcholine (ACh) is the principal vestibular efferent neurotransmitter among mammalians. Pharmacologic studies prove that ACh activates a small conductance Ca2+-activated K+ channels (KCa) current (SK2), mediated by α9-containing nicotinic ACh receptor (α9nAChR) in mammalian type II vestibular hair cells (VHCs II). However, our studies demonstrate that the m2 muscarinic ACh receptor (m2mAChR) mediates a big conductance KCa current (BK) in VHCs II. To better elucidate the correlation between these two distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Changing HC holding potentials from -90 to -60 to -40 mV, resulted in the typical waveform changes from inward to biphasic to outward currents, as have been described in mammalian and non-mammalian studies (Art et al 1982;Art et al 1984;Glowatzki and Fuchs 2000) and suggests a similar relative contribution of nAChRs and SK channels to the efferent response as found before. Muscarinic AChR effects have been found in vestibular hair cells also (Jordan et al 2013;Li et al 2007;Poppi et al 2020;Zhou et al 2013), however in the study here the recorded HC synaptic activity is clearly mediated by α9-containing nAChRs as even the potentiated response to a pulse train could be mostly inhibited with strychnine, a blocker for α9-containing nAChRs. This does not exclude that additional mAChR effects on type II HCs exist.…”
Section: Conserved Efferent Mechanisms In the Vestibular And Auditorysupporting
confidence: 40%
“…Changing HC holding potentials from -90 to -60 to -40 mV, resulted in the typical waveform changes from inward to biphasic to outward currents, as have been described in mammalian and non-mammalian studies (Art et al 1982;Art et al 1984;Glowatzki and Fuchs 2000) and suggests a similar relative contribution of nAChRs and SK channels to the efferent response as found before. Muscarinic AChR effects have been found in vestibular hair cells also (Jordan et al 2013;Li et al 2007;Poppi et al 2020;Zhou et al 2013), however in the study here the recorded HC synaptic activity is clearly mediated by α9-containing nAChRs as even the potentiated response to a pulse train could be mostly inhibited with strychnine, a blocker for α9-containing nAChRs. This does not exclude that additional mAChR effects on type II HCs exist.…”
Section: Conserved Efferent Mechanisms In the Vestibular And Auditorysupporting
confidence: 40%
“…2 G ). Better recovery of the slow/indirect VOR component in type α9 −/− mice could be explained by an increase of excitatory influences to central neurons in VNs due to inactivation of efferent-mediated hyperpolarization on type II hair cells and subsequent afferent inhibition [10,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Release of ACh due to EVS stimulation does act via α9/α10 nAChRs on type II hair cells, leading to Ca 2+ influx, activation of Ca 2+ -dependent potassium channels, and a rise of potassium efflux, which in turn causes hyperpolarization of type II hair cells. This hyperpolarization subsequently reduces Ca 2+ influx, mainly through action on voltage-dependent calcium channels, thereby reducing depolarization of hair cells [10,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Each efferent axon branches profusely in the vestibular neuroepithelium (Purcell and Perachio, 1997) to innervate Type II hair cells and afferent boutons and calyx terminals (Goldberg et al, 1990a). Recent studies have shown that cochlear and vestibular hair cells express ␣9␣10 AChR (Hiel et al, 1996;Katz et al, 2004) that has an inhibitory effect (Glowatzki and Fuchs, 2000;Wersinger and Fuchs, 2011;Zhou et al, 2013;Poppi et al, 2018). On the other hand, calyx terminals express excitatory ␣4␤2 or ␣6␤2 AChR (Holt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%